The Demise of the Dollar? - Benjamin J. Cohen (Revue de la Régulation)
The aim of this article is to explain why, despite decades of doubts, the US dollar remains the world’s top currency, and more importantly, why it is likely to remain on top for years more to come. I argue that the dollar is the indispensable currency: the one money that the world cannot do without. The dollar offers unique advantages that are unmatched by any other currency. The essay begins with a review of the attributes that are most essential to the international status of a currency. Only the dollar embodies the full list of attributes that make a currency internationally competitive. The euro and renminbi, by contrast, are seriously lacking in one or more respects. For the foreseeable future the greenback will remain dominant, as it has done for decades.